A Study on Attitude of Urban and Rural College Students Towards Science - Swarali Sanjay Shah (ASEAN Journal of Science and Engineering Education, 2022)
There is a great need to identify and develop a positive attitude towards science subject of students. The time has come to increase our efforts to develop a positive attitude towards science subjects among teachers and students. This paper reports on the attitude of students towards science. The sample consisted of 1080 students of the Madurai revenue district, India. A scale on attitude towards science was used to get the data from the students. Percentage Analysis, Mean, Standard Deviation, and t-tests were used for analyzing the data. The results showed that there is no significant difference in attitude towards science of urban and rural students.